ANALISIS PEMANFATAN MOBILE COMMERCE UNTUK HIJAB DAN BUSANA DAERAH GEDONG TATAAN UNTUK MENINGKATKAN ASET PENJUALAN - Rita Irviani; Nur Fitri (STIE Trisna Negara OKU Timur, 2019)
In the modern era like now, technology and information are two things that are inseparable and have become human needs. The sophistication of technology that is developing at this time is not necessarily only used for industrial and intelligence purposes, but has penetrated the world of hijab and clothing. The people often use current technology to find the information they want, such as finding information about hijab and fashion trends in a certain area. The case study from this research is an area that has many places to order but still very minimal information about the place. So that many people who want to know about the development of hijab and clothing today but do not know the good recommended items or not to wear. The purpose of this research is to apply the Mobile Web method to process an application that is easy and effective for use by all users of this application